Perovskite single crystal material and preparation method thereof
By preparing (C4H8O2)2MnBr2 perovskite single crystal material, the problem of unstable existing lead-based metal halide perovskite materials under environmental conditions is solved, and the effect of high fluorescence quantum yield and stable red emission is achieved, avoiding the The use of heavy metal lead.
Patent Information
- Application Number
- CN202411417837.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lead-based metal halide perovskite materials are unstable under environmental conditions, and the high toxicity of heavy metal lead limits its application, making it difficult to find alternative materials with high fluorescence quantum yields and stable red emissions.
(C4H8O2)2MnBr2 is used as perovskite single crystal material, and is prepared by the slow volatilization crystallization method of solvent. The conditions are mild, the process is simple, and the green and environmentally friendly, and a material with high fluorescence quantum yield and stable red emission is obtained.
It has achieved stable red emission at an excitation wavelength of 302nm, and the material has a high fluorescence quantum yield, avoiding the use of heavy metal lead and improving the environmental stability of the material.
Smart Images

Figure CN119392376A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor material preparation, and in particular relates to a perovskite single crystal material and a preparation method thereof. Background Art
[0002] In recent years, organic-inorganic hybrid metal halide perovskites, especially lead-based metal halide perovskites, have attracted great attention due to their excellent carrier mobility, strong absorption coefficient, long carrier diffusion length and high fluorescence intensity. They have been widely studied in the fields of solar cells, photodetectors, light-emitting diodes, etc. Up to now, for lead-based organic-inorganic hybrid metal halide perovskites, researchers have synthesized perovskite single crystals with a variety of emission colors, and their emission spectra can cover the blue to red region. However, compared with other emission colors, the choice of lead-based metal halide perovskites with extremely high fluorescence quantum yield and stability in the environment is still very limited. This is because APbI3 (A=MA, FA, Cs) exists in four crystal phases, namely α cubic phase, β tetragonal metastable phase, γ orthorhombic metastable phase and δ orthorhombic phase. The α cubic phase is a thermodynamically stable phase that is only stable at high temperatures. At room temperature and in water and oxygen conditions, it will quickly transform into a yellow δ orthorhombic non-perovskite phase composed of one-dimensional chains, which will cause the red emission to disappear. At the same time, the high toxicity of heavy metal lead also severely limits its practical application.
[0003] Metallic Sn and Pb belong to the same main group IVA. Due to its environmentally friendly properties, it is expected to be a substitute for Pb-based perovskites and has received widespread attention in photovoltaic and optoelectronic applications. 2+ Organic-inorganic hybrid metal halide perovskites show excellent emission properties, but Sn 2+ Under ambient conditions, it is easily oxidized to Sn 4+ , which will lead to the destruction of the perovskite structure and a significant attenuation of performance. At the same time, the synthesis conditions are relatively harsh and can only be carried out in an inert atmosphere.
[0004] Therefore, it is necessary to provide a new perovskite single crystal material to solve the deficiencies in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a perovskite single crystal material and a preparation method thereof. The perovskite single crystal material ((C4H8O2)2MnBr2) in the present invention has a high fluorescence quantum yield and has stable red emission at an excitation wavelength of 302nm.
[0006] In a first aspect, the present invention provides a perovskite single crystal material, the molecular formula of the perovskite single crystal material is (C4H8O2)2MnBr2.
[0007] In the present invention, the perovskite single crystal material is a single crystal material with a new structure, which not only has a high fluorescence quantum yield, but also has stable red emission at an excitation wavelength of 302nm.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned perovskite single crystal material, comprising the following steps: S1, grinding MnBr2 powder, drying it, and adding an acid solution to dissolve it to obtain a MnBr2 solution; S2, adding 1,4-dioxane solution to the MnBr2 solution, then heating and dissolving it until the solution is clear and transparent, and then volatilizing it to obtain coarse crystals; S3, washing the coarse crystals, and then drying them in an inert atmosphere to obtain a perovskite single crystal material.
[0009] In the present invention, cheap and easily available MnBr2 and 1,4-dioxane solution are used as raw materials, and a (C4H8O2)2MnBr2 single crystal material is prepared by a slow solvent evaporation crystallization method. The entire preparation process has mild conditions, simple technology, and is green and environmentally friendly. The prepared (C4H8O2)2MnBr2 single crystal material has a high fluorescence quantum yield and stable red emission at an excitation wavelength of 302nm.
[0010] In some embodiments, in step S1, the grinding treatment time is 20-40 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min or other values within the range.
[0011] It should be noted that the grinding process and time can be adjusted according to actual use needs. For example, manual grinding or mechanical grinding can be used, and the grinding time is preferably 20-40 minutes.
[0012] In some embodiments, in step S1, the acid solution is a hydrobromic acid solution, and the dissolution temperature is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C or other values within the range; the time is 0.5-1.5h, for example, 0.5h, 1h, 1.5h or other values within the range.
[0013] In the present invention, the acid solution is added to facilitate the dissolution of MnBr2 powder. At the same time, the dissolution temperature is controlled within a certain range to further accelerate the dissolution rate. The amount of hydrobromic acid solution added can be conventionally adjusted according to actual use needs.
[0014] In some embodiments, in step S2, the molar volume ratio of MnBr2 in the MnBr2 solution and the 1,4-dioxane solution is (0.5-1.5 mmol): (1-6 mL), for example, it can be 0.5 mmol:1 mL, 0.5 mmol:3 mL, 0.5 mmol:6 mL, 1 mmol:1 mL, 1 mmol:3 mL, 1 mmol:6 mL, 1.5 mmol:1 mL, 1.5 mmol:3 mL, 1.5 mmol:6 mL or other ratios within this range.
[0015] In the present invention, by controlling the amount-to-volume ratio of MnBr2 and 1,4-dioxane solution within a specific range, a perovskite single crystal material with a specific structure can be obtained.
[0016] In some embodiments, in step S2, the temperature for heating and dissolving is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C or other values within this range.
[0017] In some embodiments, in step S2, the volatilization treatment temperature is 10-50°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C or other values within the range; the time is 3-5d, for example, 3d, 4d, 5d or other values within the range.
[0018] In the present invention, the fluorescence quantum yield of the perovskite single crystal material can be improved by controlling the temperature of the volatilization treatment within a specific range.
[0019] In some embodiments, in step S3, washing specifically includes: first rinsing the crude crystals with a first organic solvent, and then rinsing the crude crystals with a second organic solvent; wherein the first organic solvent includes isopropanol and / or ethanol, and the second organic solvent is n-hexane.
[0020] It should be noted that the washing solvent can be conventionally adjusted according to actual use needs. In the present invention, the first organic solvent preferably includes isopropanol and ethanol, and propanol and ethanol can be mixed in any proportion; the second organic solvent is preferably n-hexane; during the washing process, the number of rinses of the first organic solvent and the second organic solvent can be conventionally adjusted, for example, the first organic solvent is preferably rinsed 3-4 times.
[0021] In some embodiments, in step S3, the inert gas is nitrogen.
[0022] It should be noted that the inert gas can be conventionally adjusted according to actual use needs, for example, it can be argon and nitrogen. In the present invention, the inert gas is preferably nitrogen.
[0023] In some embodiments, in step S3, the drying treatment temperature is 50-85°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or other values within this range; the time is 20-40min, for example, it can be 20min, 25min, 30min, 35min, 40min or other values within this range.
[0024] In the present invention, the fluorescence quantum yield of the perovskite single crystal material can be further improved by controlling the temperature of the drying process within a specific range.
[0025] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention provides a perovskite single crystal material ((C4H8O2)2MnBr2) with a new structure, which not only has a high fluorescence quantum yield, but also has stable red emission at an excitation wavelength of 302nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD spectrum of the (C4H8O2)2MnBr2 single crystal material prepared in Example 1 of the present invention; Figure 2 Schematic diagram of the structure of the (C4H8O2)2MnBr2 single crystal material prepared in Example 1 of the present invention; Figure 3 The fluorescence excitation and emission spectra of the (C4H8O2)2MnBr2 single crystal material prepared in Example 1 of the present invention; Figure 4 This is the ultraviolet-visible absorption spectrum of the (C4H8O2)2MnBr2 single crystal material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0029] Example 1 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 2 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent, and then quickly transfer to a constant temperature environment of 10°C and slowly evaporate for 4 days to obtain crude crystals; S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 50° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0030] The perovskite single crystal material (structure as shown in FIG. Figure 2 As shown in the figure, XRD, fluorescence excitation and fluorescence emission, and UV-visible absorption spectrum tests were performed respectively, and the results were as follows Figure 1 , 3 and 4.
[0031] from Figure 1 It can be seen that the molecular formula of the perovskite single crystal material prepared by the present invention is (C4H8O2)2MnBr2. Figure 3 It can be seen that at an excitation wavelength of 302 nm, the (C4H8O2)2MnBr2 single crystal material has stable red emission. Figure 4 It can be seen that the (C4H8O2)2MnBr2 single crystal material has certain absorption in the ultraviolet absorption band.
[0032] Example 2 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 1 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve it at 70°C until the solution is clear and transparent. Then quickly transfer it to a constant temperature environment of 10°C and slowly evaporate it for 4 days to obtain crude crystals. S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 50° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0033] Example 3 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 6 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent, and then quickly transfer to a constant temperature environment of 10°C and slowly evaporate for 4 days to obtain crude crystals; S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 50° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0034] Example 4 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 2 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent. Then quickly transfer to a constant temperature environment of 30°C and slowly evaporate for 4 days to obtain crude crystals. S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 50° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0035] Example 5 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 2 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent, and then quickly transfer to a constant temperature environment of 45°C, and slowly evaporate for 4 days to obtain crude crystals; S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 50° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0036] Example 6 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 2 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent, and then quickly transfer to a constant temperature environment of 10°C and slowly evaporate for 4 days to obtain crude crystals; S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 65° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0037] Example 7 A method for preparing a perovskite single crystal material comprises the following steps: S1. First, weigh 1 mmol of MnBr2 powder in a mortar in a glove box, grind it for 30 min, and then transfer it to a 20 mL glass bottle. Dry the powder with an infrared lamp, then add 1.5 mL of hydrobromic acid solution to the glass bottle, and heat and dissolve it at 90 ° C for 1 h to obtain a MnBr2 solution. S2. Add 2 mL of 1,4-dioxane solution to the MnBr2 solution, and then heat and dissolve at 70°C until the solution is clear and transparent, and then quickly transfer to a constant temperature environment of 10°C and slowly evaporate for 4 days to obtain crude crystals; S3. Wash the crude crystals obtained in step S2 three times with a mixed solvent of isopropanol and ethanol, then rinse the crystals with n-hexane solvent, and finally dry the crystals on a hot plate at 85° C. in a glove box filled with nitrogen for 30 minutes to obtain a perovskite single crystal material.
[0038] Comparative Example 1 The preparation method of the perovskite single crystal material in this comparative example is basically the same as that in Example 1, except that in step S2, the volatilization temperature is 60°C.
[0039] Comparative Example 2 The preparation method of the perovskite single crystal material in this comparative example is basically the same as that in Example 1, except that in step S3, the drying temperature is 100°C.
[0040] Performance Testing The fluorescence quantum yield of the perovskite single crystal materials prepared in Examples 1-7 and Comparative Examples 1-2 was tested, and the results are shown in Table 1 below: Table 1 Fluorescence quantum yield results of perovskite single crystal materials
[0041] It can be seen from Table 1 that the perovskite single crystal materials prepared in Examples 1-7 have a higher fluorescence quantum yield. The volatilization temperature in Comparative Example 1 is higher and the drying temperature in Comparative Example 2 is higher. It is found that the fluorescence quantum yield of the prepared perovskite single crystal material is significantly reduced. The results further show that in the present invention, the fluorescence quantum yield of the prepared perovskite single crystal material can be improved by controlling the volatilization temperature and the drying temperature within a specific range.
[0042] In summary, the perovskite single crystal material ((C4H8O2)2MnBr2) provided by the present invention not only has a high fluorescence quantum yield, but also has stable red emission at an excitation wavelength of 302nm.
[0043] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0044] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite single crystal material, characterized in that: The molecular formula of the perovskite single crystal material is (C4H8O2)2MnBr2.
2. A method for preparing a perovskite single crystal material as claimed in claim 1, characterized in that: The steps include: S1, grinding the MnBr2 powder, drying it, adding an acid solution to dissolve it, and obtaining a MnBr2 solution; S2, adding 1,4-dioxane solution to the MnBr2 solution, and then heating and dissolving until the solution is clear and transparent, and then volatilizing to obtain crude crystals; S3, washing the crude crystals, and then drying them under an inert atmosphere to obtain a perovskite single crystal material.
3. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S1, the grinding process lasts for 20-40 minutes.
4. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S1, the acid solution is a hydrobromic acid solution, and the dissolution temperature is 80-100°C and the dissolution time is 0.5-1.5h.
5. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S2, the molar volume ratio of MnBr2 in the MnBr2 solution and the 1,4-dioxane solution is (0.5-1.5 mmol): (1-6 mL).
6. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S2, the temperature for heating and dissolving is 60-80°C.
7. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S2, the volatilization treatment is carried out at a temperature of 10-50°C and for a time of 3-5 days.
8. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S3, the washing specifically includes: firstly washing the crude crystals with a first organic solvent, and then washing the crude crystals with a second organic solvent; Wherein, the first organic solvent includes isopropanol and / or ethanol, and the second organic solvent is n-hexane.
9. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S3, the inert gas is nitrogen.
10. The method for preparing a perovskite single crystal material according to claim 2, characterized in that: In step S3, the drying process is carried out at a temperature of 50-85°C and for a time of 20-40 minutes.
Citation Information
Patent Citations
Dioxane-coordinated rare-earth coordination compound, and preparation method and application thereof
CN102153575A
Transition metal-doped carbon fluorescent quantum dot preparation method
CN106147760A
Organic-inorganic hybrid zero-dimensional non-lead perovskite material and synthesis method thereof
CN111909696A